Folklore Traditions In The Epos Of Sayyadi “Tоhir And Zuhrо” (Eurasian Journal of Humanities and Social Sciences, 2022)
This article discusses the fact that Sayyadi's epic "Tahir and Zuhro" reflects the traditions of folklore, in particular, it was created on the basis of a fairy tale and became one of the most famous works in the written literature of the East. The ideological content of the epic, the images and events depicted in it, the fact that Sayyodi was well acquainted with the examples of folklore and skillfully used the achievements of folklore in the creation of his work were studied in detail.